DIGITAL STORYTELLING: TEACHERS' GUIDE TO ATTRACT CHILDREN'S INTEREST AND MOTIVATION IN KINDERGARTEN'S ENGLISH LANGUAGE LEARNING - Mozes Kurniawan (Universitas Kristen Satya Wacana, 2021)
Learning English among early childhood is increasingly being presented in many schools. To meet the needs of the times, mastery of English particularly vocabulary has become a new concern to be accommodated in education especially for children in concern to the characteristics of early childhood learning. Preliminary research on two kindergarten-level classes (age of 5 to 6) in a private school showed that there were several problems teachers faced when applying the conventional storytelling method. The alternative solution to this problem is implementing digital storytelling method which is integrating storytelling and digital technology. This research is based on data obtained qualitatively so that it gives the characteristics of descriptive qualitative research that wants to explain the phenomenon of the object of research according to the topic. The data in this study were obtained from the results of field observations in the classroom when the learning process took place. The result showed that digital storytelling method is considered to be able to attract children's attention in following the stories and learning materials brought by the teacher. Student motivation also appears to emerge with the application of the digital storytelling method in learning English. There are also some teachers' guide to apply this method in English language learning for kids.